2007
DOI: 10.1354/vp.44-6-921
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Lymphomatoid Granulomatosis in a Dog: Evidence of Immunophenotypic Diversity and Relationship to Human Pulmonary Lymphomatoid Granulomatosis and Pulmonary Hodgkin's Disease

Abstract: Abstract. We describe a 10-month-old, intact female American Cocker Spaniel with pulmonary lymphomatoid granulomatosis (PLG). On clinical examination, this dog presented with nonproductive dry cough, serous nasal discharge, dyspnea, and lack of appetite. Radiography showed a consolidated lesion in the left cranial lung lobe. Histopathologic examination showed a mixed population of atypical lymphoid cells that had infiltrated into the pulmonary blood vessels angiocentrically. The lymphocytes were CD3 positive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…The immunophenotypic findings indicated that AIL in the cat in the current study was of both B-and T-cell lineages, and these findings correlated with those reported for 1 case of canine pulmonary AIL 18 and for other types of canine lymphoma. 20,23,24 These findings were in contrast to human AIL, where most cases have been classified as Tcell-rich B-cell lymphomas.…”
supporting
confidence: 90%
“…The immunophenotypic findings indicated that AIL in the cat in the current study was of both B-and T-cell lineages, and these findings correlated with those reported for 1 case of canine pulmonary AIL 18 and for other types of canine lymphoma. 20,23,24 These findings were in contrast to human AIL, where most cases have been classified as Tcell-rich B-cell lymphomas.…”
supporting
confidence: 90%
“…There was no evidence of hepatomegaly or splenomegaly. A complete blood count showed abnormal leukocytosis (40,100 cell/µl; reference range 6,000 to 17,000/µl) with mature neutrophilia (23,258 cell/µl; reference range 3,000 to 11,500 /µl) and lymphocytosis (16,441 cell/µl reference range 1,000 to 4,800/µl). The blood biochemical findings included an increased total protein concentration (8.4 g/dl) with a high globulin concentration (A/ G=0.5).…”
mentioning
confidence: 99%
“…The phenotype of canine LYG is now controversial because immunohistochemical analyses of the canine LYG have been documented in only a few papers [14,16,20]. In one report, canine LYG has been associated with malignant T-cell type lymphocytes and is considered a T-cell lymphoma [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present study could not examine the particular immunophenotype (CD4, CD8, TCRαβ and TCRγδ) of neoplastic T-cell lymphocytes, as fresh specimens of the tumor were unavailable. No reports have described tumor cell expression for CD4 or CD8 in canine vasotropic and vasoinvasive nonepitheliotropic lymphoma, although CD4-positive cells are reportedly dominant in human cases [10,11]. As a result, the neoplastic vascular invasion and destruction observed in this case caused ischemic necrosis of neoplastic and non-neoplastic tissues in the skin, representing a characteristic feature of vasotropic and vasoinvasive nonepitheliotropic lymphoma.…”
mentioning
confidence: 78%